Transformations : a region in the making - Reyes, Vicente C., Jr.; Shie, Tamara Renee ;Lizaso, Marcelino N. Jr. (Manila, Philippines : Far Eastern University Publications, 2004)
The Diamond Book Series is a joint project of Fra Eastern University and FEU Alumni Foundation, Inc.
Part I. Transformations : History, Authority and Organization. -- Part II. Transformations : Country and Comparative Studies -- Part III. Transformations : ASEAN, Regionalism and AFTA -- Part IV. Transformations : International Relations in the Region -- Part V. Book Review and Research Notes. 1. Transformations: History, Authority and Organization -- The Forgotten Heroes: Transformations of Historians' Views on Peasant Protests in the Philippine / Novita Dewi -- Fiscal Decentralization, Incentives and Growth in the Philippines / Euben C. Paracuelles -- Bureaucracies and Networks: Organizational Transformations in an Australian Setting / Vicente Chua Reyes, Jr. -- 2. Transformations: Country and Comparative Studies -- The World Bank Structural Adjustment Lending Program: A Comparative Study of Thailand and the Philippines / Ferdinand P. Uko -- East Timor: From a New-Born Nation-State to an Adult Southeast Asian Actor / Elsa Ferreira Whitehead -- Transformation of Malay Muslims in South Thailand into the Thai Nation / Choo Teik Choon -- 3. Transformations: ASEAN, Regionalism and AFTA -- AFTA: Challenges and Prospects / Sopaporn Saeung -- Politics of ASEAN-China Free Trade Area Agreement / Jiang Yang Jo -- 4. Transformations: International Relations in the Region -- The Chinese Economic Threat: Hype or Harbinger for Southeast Asia / Tamara Renee Shie -- Re-imposing Secularization: US Anti-terrorist Campaign / Joy Lam -- Redefining Terrorism and Security Communities: US-Southeast Asia Cooperation in the 'War on Terror' / Tamara Renee Shie -- 5. Book Review and Research Notes -- Book Review: The Roots of Violence in Indonesia: Contemporary Violence in Historical Perspective / Marcelino N. Lizaso, Jr. -- Revisiting the Asian Financial Crisis: Critical Review of the Economic Premises Of the Article Entitled: The End of the Asian Myth: Why Were the Experts Fooled? / Vicente C. Reyes, Jr.
Includes bibliographical references.
Keywords: SOUTHEAST ASIA